1999
DOI: 10.1183/09031936.99.14511069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theophylline, dexamethasone and salbutamol on cytokine gene expression in human peripheral blood CD4+ T-cells

Abstract: CD4+ T-cells are considered as pivotal in orchestrating the airway inflammation in asthma through the actions of their cytokines. Current hypothesis suggests that the anti-asthma effect of theophylline may be due to its anti-inflammatory actions, although the exact mechanisms remain unclear.The in vitro effect of theophylline on cytokine gene expression in peripheral blood CD4+ T-cells in normal subjects was compared with that of dexamethasone and salbutamol. CD4+ T-cells were cultured with phytohaemagglutin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
2
8
1
Order By: Relevance
“…In our study, (S,S)-formoterol had no effect on IL-4 secretion in Jurkat human T cells in contrast to its stimulatory effect on IL-4 production in mast cells, suggesting that the effect of (S,S)-formoterol on IL-4 production is cell type-specific. Our results are consistent with Choy et al’s finding [22]that albuterol did not have any effect on the expression of the IL-4 gene in human peripheral blood CD4+ T cells.…”
Section: Discussionsupporting
confidence: 83%
“…In our study, (S,S)-formoterol had no effect on IL-4 secretion in Jurkat human T cells in contrast to its stimulatory effect on IL-4 production in mast cells, suggesting that the effect of (S,S)-formoterol on IL-4 production is cell type-specific. Our results are consistent with Choy et al’s finding [22]that albuterol did not have any effect on the expression of the IL-4 gene in human peripheral blood CD4+ T cells.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, we could not confirm a cytokine dysregulation with a shift towards a preferential production of Th2 cytokines in our paediatric ALL‐cohort (Zhang et al , 2000). However, the lower production of IFNγ by T cells from patients treated with dexamethasone fits well with the known immunosuppressive effects of this steroid on T‐cell function (Choy et al , 1999) and could partly explain the increased rate of infectious complications in this patient population (Mantadakis et al , 2004). Interestingly, reduced IFNγ‐production was the only parameter associated with the application of dexamethasone while all other immune parameters, including TCR‐repertoire complexity and thymic function, were not affected by its use.…”
Section: Discussionsupporting
confidence: 55%
“…Nie et al [37] described no significant change in the level of IFN-γ in the sputum of asthmatic patients after administration of low oral dose theophylline. Choy et al [6] demonstrated that an in vitro suppression effect of theophylline on IFN-γ expression in peripheral blood CD4 Tcells in normal subjects was only seen with high concentration of theophylline (10 −3 M) and not at low concentration.…”
Section: Discussionmentioning
confidence: 98%